Why and How Did Narrative Fictions Evolve? Fictions as Entertainment Technologies - Dubourg, Edgar; Baumard, Nicolas (Frontiers in Psychology, 2022)
Narrative fictions have surely become the single most widespread source of entertainment in the world. In their free time, humans read novels and comics, watch movies and TV series, and play video games: they consume stories that they know to be false. Such behaviors are expanding at lightning speed in modern societies. Yet, the question of the origin of fictions has been an evolutionary puzzle for decades: Are fictions biological adaptations, or the by-products of cognitive mechanisms that evolved for another purpose? The absence of any consensus in cognitive science has made it difficult to explain how narrative fictions evolve culturally. We argue that current conflicting hypotheses are partly wrong, and partly right: narrative fictions are by-products of the human mind, because they obviously co-opt some pre-existing cognitive preferences and mechanisms, such as our interest for social information, and our abilities to do mindreading and to imagine counterfactuals. But humans reap some fitness benefits from producing and consuming such appealing cultural items, making fictions adaptive. To reconcile these two views, we put forward the hypothesis that narrative fictions are best seen as entertainment technologies that is, as items crafted by some people for the proximate goal to grab the attention of other people, and with the ultimate goal to fulfill other evolutionary-relevant functions that become easier once other people’s attention is caught. This hypothesis explains why fictions are filled with exaggerated and entertaining stimuli, why they fit so well the changing preferences of the audience they target, and why producers constantly make their fictions more attractive as time goes by, in a cumulative manner.